An interactive information retrieval system: |SORGU - Kural, Namık. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
There are several interactive information retrieval software packages that maintain easy access to data base items and structures. It is relatively easy for persons famil iar with computer to use these packages. But to persons who are unfamiliar, especially the managers, using these packages is not easy. The syntax of these packages is extraordinarily different for these persons and usually do not wish to spend time learning this syntax. SORGU is a turkish based interactive information retrieval software package. The queries are formed using menus. It does not have any syntax convention. Anybody who has knowledge about the fundamental concepts of data base management systems can easily use SORGU. It is a completely menu driven inquiry system that provides additional facil ities to change the item 'naming conventions, supports multiple enquiries and user defined report structures. Because of the ease of use training time is minimized.
Keywords: Information storage and retrieval systems.; Interactive computer systems.